What’s the ‘Puzzle about Belief’ ? Revisiting Kripke’s Challenge through a Fregean Lens (Aporia, 2024)
In “A Puzzle About Belief” (1979), Saul Kripke posits a thought experiment involvinga bilingual named Pierre, who comes to what seem like contradictory beliefs aboutthe city of London. On a popular reading, the upshot of how Kripke sets up Pierre’sproblem is that the challenges of ascribing propositional attitudes such as belief toanother person are more complex than suggested in previous philosophical analyses,particularly Gottlob Frege’s “Sense and Reference” (1948). In particular, Kripke aimsto show that a genuine paradox about belief ascription can arise without the needto presuppose that a thinker with different beliefs about the same object relates tothat object through different cognitive perspectives (i.e., what Frege called modes ofpresentation). In this essay, I take issue with how Kripke draws his conclusion thatPierre’s problem must go beyond Frege’s notions of sense and reference. I argue thatapplication of Fregean notions of sense indeed ‘solves’ Kripke’s puzzle about Pierreand that Kripke’s pre-emptive reply to such an objection does not suffice, castingdoubt only on how the Pierre paradox gets off the ground. In sum, I argue that acharitable understanding of Frege’s ideas and a closer interrogation of Kripke’s set-upreveals that Pierre’s ‘puzzle’ is not necessarily a puzzle.